Blood Lipid Peroxidation and DNA Damage in a Nigerian Population of type 2 Diabetics - Olaniyan, O.O. *, Osadolor, H.B. (Sokoto Journal of Medical Laboratory Science)
Diabetes mellitus is being considered as a free radical disease owing to the increase in the production of free radical and subsequent deficiency in antioxidant defense mechanisms. There are limited studies regarding lipid peroxidation and antioxidant status among Nigerian diabetics. The aim of this study was to evaluate plasma antioxidant status and Oxidative DNA damage among type 2 diabetes patients with and without vascular complications. A total of 170 age and gender- matched subjects including 120 type 2 diabetics (60 with vascular complications and 60 without vascular complications) and 50 non-diabetes apparently healthy subjects were studied. A significant increase in mean 8-OHdG level indicating DNA damage and MDA indicating lipid peroxidation were observed in parallel to a significant decrease in levels of eSOD, eGSH and TAC indicating antioxidant parameters in diabetics with and without vascular complications as compared to controls and also in diabetics with vascular complications as compared to those without vascular complications. There were positive correlations of eSOD and TAC with MDA and 8-OHdG in diabetics with vascular complications. There were significant lipid peroxidation and oxidative DNA damage in Nigerian type 2 diabetics with greater intensity among vascular complicated patients than those without vascular complications.